گاما رو نصب کن!

{{ number }}
اعلان ها
اعلان جدیدی وجود ندارد!
کاربر جدید

جستجو

پربازدیدها: #{{ tag.title }}

میتونی لایو بذاری!

اگر $f(x)=1-x-{{x}^{2}}$ و $g(x)=x+2$ باشد، ریشه‌ی معادله‌ی $\frac{fog(x)-gof(x)}{x}=-6$ کدام است؟

1 ) 

2

2 ) 

0

3 ) 

1-

4 ) 

4

پاسخ تشریحی :
نمایش پاسخ

$fog(x)=f(g(x))=f(x+2)-{{(x+2)}^{2}}=1-x-2-{{x}^{2}}-4x-4\Rightarrow fog(x)=-{{x}^{2}}-5x-5$

$gof(x)=g(f(x))=g(1-x-{{x}^{2}})=1-x-{{x}^{2}}+2=3-x-{{x}^{2}}$

$\frac{fog(x)-gof(x)}{x}=\frac{-{{x}^{2}}-5x-5-3+x+{{x}^{2}}}{x}=\frac{-4x-8}{x}=-6$

$\Rightarrow -4x-8=-6x\Rightarrow 2x=8\Rightarrow x=4$

تحلیل ویدئویی تست

جواد راستگویان